Multivalued starlike functions of complex order - Çağlar, Mert; Owa, Shigeyoshi; Şen, Arzu; YAVUZ, EMEL; POLATOĞLU, YAŞAR (My University, 2008)
Let Aα be the class of functions f(z) = z α (z + a2z 2 + · · ·) which are analytic in the open unit disc U. For f(z) ∈ Aα using the fractional calculus, a subclass S ∗ α (1−b) which is the class of starlike functions of complex order (1−b) is introduced. The object of the present paper is to discuss some properties for f(z) belonging to the class S ∗ α (1 − b). 2000 Mathematics Subject Classification: 30C45
Keywords: fractional calculus; analytic function; starlike of complex order; subordination